Food for Thought: Review of Just Fodder (2022) and Food, Justice, and Animals (2023) by Josh Milburn - Salzani, Carlo; Weisberg, Zipporah (Humanimalia, 2025)
Review of:Josh Milburn, Just Fodder: The Ethics of Feeding Animals. Montreal & Kingston: McGill-Queen’s University Press, 2022. viii + 232 pp. CA$37.95 (pb)andJosh Milburn, Food, Justice, and Animals: Feeding the World Respectfully. Oxford: Oxford University Press, 2023. vi + 216 pp. £70.00 (hb).